Decorative sheet
Patent Information
- Application Number
- JP2020206909
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-12-14
AI Technical Summary
【0018】 本発明によれば、高い硬度を有するとともに、耐摩擦性に優れた表面保護層を有する化粧シートを提供することが可能となる。
Smart Images

Figure 0007651851000003 
Figure 0007651851000004 
Figure 0007651851000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a decorative sheet. [Background technology]
[0002] Generally, decorative sheets are intended to protect and decorate the surface of adherends such as wooden boards, and are used by attaching the decorative sheet to the surface of the adherend. Decorative boards equipped with decorative sheets are used in various building materials, furniture, etc.
[0003] A decorative sheet is provided with a surface protective layer for protecting the outermost surface. Since the surface protective layer may come into contact with various liquids or solids, it is necessary for the layer to have durability such as scratch resistance and stain resistance (soiling resistance).
[0004] Furthermore, in recent years, due to growing environmental awareness, there has been a shift not only to solvents but also to polyolefin resins such as polypropylene and polyethylene as base sheets for decorative sheets.
[0005] However, even polyolefin resins have insufficient abrasion resistance compared to polyvinyl chloride, so in order to meet the required characteristics, a surface protective layer is often provided on the outermost layer of the decorative sheet.
[0006] On the other hand, from the viewpoint of environmental impact, attention has been paid to the fact that, conventionally, surface protective layers and the like have been formed from solvent-based coating agents containing aromatic solvents such as toluene and xylene, and aliphatic solvents such as methyl ethyl ketone and ethyl acetate, as disclosed in Patent Document 1, for example.
[0007] Aromatic solvents, aliphatic solvents, etc. are all volatile organic compounds (VOCs), and aromatic solvents such as toluene and xylene in particular are listed as designated chemical substances under the PRTR Law and as substances for which guideline values for chemical substances in indoor air are established. In addition, problems have been pointed out regarding the work environment caused by the volatilization of VOCs contained in solvent-based coating agents during the manufacture of decorative sheets, and environmental safety problems caused by residual VOCs being dispersed into general living spaces when decorative sheets are used. For this reason, reducing the amount of VOCs used in decorative sheets has become a recent issue.
[0008] Therefore, solvent-based coating agents are used as coating agents for forming the surface protective layer, but in recent years, there has been a growing demand for water-based coating agents that use as little organic solvent as possible.
[0009] As an aqueous coating agent, for example, as disclosed in Patent Document 2, one using an aqueous acrylic resin is known.
[0010] However, water-based acrylic resin-based water-based coating agents tend to have a surface protective layer that is inferior in abrasion resistance and adhesion to polyolefin resins compared to solvent-based coating agents.
[0011] Meanwhile, in order to improve the drawbacks, it has been proposed to use an aqueous acrylic-urethane copolymer composition as an aqueous coating agent, as disclosed in, for example, Patent Document 3. The surface protective layer formed using the aqueous acrylic-urethane copolymer composition has improved abrasion resistance and adhesion to polyolefin resins. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Japanese Patent Application Publication No. 11-198309 [Patent Document 2] Japanese Patent Application Publication No. 9-158098 [Patent Document 3] JP 2000-119362 A Summary of the Invention [Problem to be solved by the invention]
[0013] However, the surface protective layer formed using the aqueous acrylic-urethane copolymer composition as disclosed in Patent Document 3 has insufficient blocking properties, and there is a problem in that the surface protective layer adheres to adjacent layers when the decorative sheet is rolled up.
[0014] Furthermore, the surface protective layer formed using an aqueous acrylic resin as disclosed in Patent Document 2 and the surface protective layer formed using an aqueous acrylic-urethane copolymer composition as disclosed in Patent Document 3 are also insufficient in terms of stain resistance.
[0015] Furthermore, there is an increasing demand for environmentally friendly materials and manufacturing methods not only for decorative sheets but also for various industrial products. In recent years, environmental problems such as the burden on the global environment, the depletion of fossil resources, and waste disposal have become more serious, and there is a demand for material development that effectively utilizes natural resources instead of fossil resources. Among them, cellulose-based materials have attracted attention as the most widely produced biomass material on earth and as a material that is biodegradable in the natural environment. In particular, nanofibrous cellulose, which has high transparency in addition to high strength, high elastic modulus, high crystallinity, and low coefficient of linear thermal expansion, which are characteristics of cellulose, is expected to be used as a new cellulose material for functional materials.
[0016] In order to solve the problems associated with decorative sheets, the present invention aims to provide a decorative sheet that uses microfibrillated cellulose, a material derived from natural resources, and that has high hardness and a surface protective layer that is excellent in abrasion resistance. [Means for solving the problem]
[0017] In order to solve the problems, one aspect of the present invention is a decorative sheet having a surface protective layer. The surface protective layer includes an aqueous polyurethane resin composition and a composite particle. The composite particle has a coating layer made of fine cellulose. Core particles containing at least one type of polymer are disposed on the surface of the fine cellulose. Effect of the Invention
[0018] According to the present invention, it is possible to provide a decorative sheet having a surface protective layer that has high hardness and excellent abrasion resistance. [Brief description of the drawings]
[0019] [Figure 1] 1 is a schematic cross-sectional view of a decorative sheet according to a first embodiment. [Diagram 2] FIG. 1 is a schematic diagram of a composite particle according to a first embodiment. [Diagram 3] FIG. 1 is a schematic diagram of an O / W type Pickering emulsion using microfibrillated cellulose according to the first embodiment, a composite particle obtained by solidifying a polymerizable monomer or polymer inside the emulsion, and a composite particle obtained by adding a functional component to the coating layer of the composite particle. [Figure 4] FIG. 2 is a diagram showing the results of observing the composite particles obtained in Example 1 with a scanning electron microscope. [Diagram 5] FIG. 2 is a diagram showing the results of observing the composite particles obtained in Example 1 at a high magnification using a scanning electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present technology will be described with reference to the drawings. In the description of the drawings, the same or similar parts are given the same or similar symbols, and duplicate descriptions are omitted. Each drawing is schematic and may differ from the actual one. The embodiments shown below are examples of devices and methods for embodying the technical idea of the present technology, and the technical idea of the present technology is not limited to the devices and methods exemplified in the following embodiments. The technical idea of the present technology can be modified in various ways within the technical scope described in the claims.
[0021] (First embodiment) As shown in FIG. 1, the decorative sheet 1 has a substrate 2 sheet and a surface protective layer 3 .
[0022] <Base sheet> The base sheet 2 has a pattern layer or the like (not shown) laminated on the surface (front surface).
[0023] For example, a thermoplastic resin can be used as the material of the base sheet 2. Specifically, polyvinyl chloride, polyethylene terephthalate, polybutylene terephthalate, polyamide, polyethylene, polypropylene, polycarbonate, polyethylene naphthalate, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, ionomer, acrylic acid ester, methacrylic acid ester, etc. Also, polyolefin resins such as polypropylene and polyethylene can be used.
[0024] The base sheet 2 may be colored. When the base sheet 2 is colored, a coloring material (pigment or dye) is added to the thermoplastic resin to color it. As the coloring agent, for example, inorganic pigments such as titanium dioxide, carbon black, iron oxide, etc., organic pigments such as phthalocyanine blue, etc., as well as various dyes can be used. One or more types of coloring agents can be selected from publicly known or commercially available coloring agents. The amount of coloring agent added can also be appropriately set according to the desired color tone, etc.
[0025] The base sheet 2 may contain various additives, such as a filler, a matting agent, a foaming agent, a flame retardant, a lubricant, an antistatic agent, an antioxidant, an ultraviolet absorbing agent, and a light stabilizer, as required.
[0026] The thickness of the base sheet 2 is appropriately set depending on the application and method of use of the final product, but is generally preferably within the range of 50 μm to 250 μm.
[0027] If necessary, the surface of the base sheet 2 may be subjected to a corona discharge treatment in order to improve the adhesion of the ink that forms the design layer. The corona discharge treatment may be performed by a known method and under known conditions.
[0028] <Pattern layer> The pattern layer imparts a desired pattern (design) to the decorative sheet 1, and the type of pattern is not limited. Examples of the types of patterns include wood grain patterns, stone grain patterns, sand grain patterns, tile patterns, brickwork patterns, fabric patterns, leather-stained patterns, geometric figures, letters, symbols, and abstract patterns.
[0029] The method for forming the design layer is not particularly limited, and for example, the design layer may be formed on the surface of the base sheet 2 by a printing method using ink obtained by dissolving (or dispersing) a known colorant (dye or pigment) together with a binder resin in a solvent (or dispersion medium). From the viewpoint of reducing the VOC of the decorative sheet 1, it is desirable to use an aqueous composition as the ink.
[0030] Examples of colorants that can be used include inorganic pigments such as carbon black, titanium white, zinc oxide, red iron oxide, iron blue, and cadmium red; organic pigments such as azo pigments, lake pigments, anthraquinone pigments, quinacridone pigments, phthalocyanine pigments, isoindolinone pigments, and dioxazine pigments; metal powder pigments such as aluminum powder and bronze powder; pearlescent pigments such as titanium oxide-coated mica and bismuth oxide chloride; fluorescent pigments; and luminous pigments. The colorants can be used alone or in combination of two or more. The colorants may further contain fillers such as silica, extender pigments such as organic beads, neutralizers, surfactants, and the like.
[0031] As the binder resin, in addition to the polyester-based urethane resin that has been hydrophilically treated, polyester, polyacrylate, polyvinyl acetate, polybutadiene, polyvinyl chloride, chlorinated polypropylene, polyethylene, polystyrene, polystyrene-acrylate copolymer, rosin derivative, alcohol adduct of styrene-maleic anhydride copolymer, cellulose-based resin, etc. can also be used. More specifically, for example, polyacrylamide-based resin, poly(meth)acrylic acid-based resin, polyethylene oxide-based resin, poly N-vinylpyrrolidone-based resin, water-soluble polyester-based resin, water-soluble polyamide-based resin, water-soluble amino-based resin, water-soluble phenol-based resin, other water-soluble synthetic resin, water-soluble natural polymer such as polynucleotide, polypeptide, polysaccharide, etc. can also be used. In addition, for example, natural rubber, synthetic rubber, polyvinyl acetate-based resin, (meth)acrylic resin, polyvinyl chloride-based resin, polyurethane-polyacrylic resin modified or mixed resin, and other resins can also be used. The binder resin can be used alone or in combination of two or more kinds.
[0032] Examples of printing methods that can be used to form the design layer include gravure printing, offset printing, screen printing, flexographic printing, electrostatic printing, and inkjet printing. When forming a solid design layer over the entire surface, various coating methods can be used, such as roll coating, knife coating, air knife coating, die coating, lip coating, comma coating, kiss coating, flow coating, and dip coating. In addition, hand-drawing, ink-flowing, photography, transfer printing, laser beam drawing, electron beam drawing, partial deposition of metals, etching, and the like may be used, and may be used in combination with other forming methods.
[0033] The thickness of the design layer is not particularly limited and can be set appropriately depending on the product characteristics, but the thickness of the design layer at the time of coating is, for example, in the range of 1 μm to 15 μm, and the thickness of the design layer after drying is, for example, in the range of 0.1 μm to 10 μm.
[0034] <Surface protective layer> The surface protective layer 3 includes composite particles 4 and a binder matrix 5 . Moreover, the surface protective layer 3 has an embossed pattern (not shown) formed on the surface that forms the outermost surface of the decorative sheet (the upper surface in FIG. 1).
[0035] <Emboss> The embossing process for forming the embossed pattern is carried out in order to impart a desired texture, such as the surface of wood, to the decorative sheet 1. In addition, the embossing process is carried out, for example, by heating and softening the decorative sheet 1 on a heated drum, heating the softened decorative sheet 1 to a temperature range of 160°C to 180°C using an infrared radiant heater, and then pressing and shaping the sheet using an embossing plate having a desired uneven pattern, followed by cooling and fixing. The embossing process can be carried out, for example, using a known sheet-fed or rotary embossing machine. Examples of the uneven pattern include wood grain vessel grooves, embossed patterns (uneven patterns of raised annual rings), hairlines, sand grain, and matte finish, from which a desired pattern can be appropriately selected.
[0036] There are no particular limitations on the method for forming the surface protection layer 3 using a composition in which the composite particles 4 and the binder matrix 5 are mixed. Since the composition has fluidity, for example, the surface protection layer 3 is formed by wet-coating the composition onto the base sheet 2 and curing the coating.
[0037] A known method can be used as a method for coating the composition obtained by mixing the composite particles 4 and the binder matrix 5 onto the base sheet 2. Specifically, a bar coating method, a dip coating method, a spin coating method, a flow coating method, a spray coating method, a roll coating method, a gravure roll coating method, an air doctor coating method, a blade coating method, a wire doctor coating method, a knife coating method, a reverse coating method, a transfer roll coating method, a microgravure coating method, a kiss coating method, a cast coating method, a slot orifice coating method, a calendar coating method, a die coating method, or the like can be used.
[0038] <Composite particles> As shown in FIG. 2, the composite particle 4 has a core particle 8 and a coating layer 7. The core particle 8 is a particle containing at least one type of polymer. The coating layer 7 is a layer that coats the surface of the core particle 8, and is configured to contain micronized cellulose 6. In the following description, "micronized cellulose" may be referred to as "cellulose nanofiber" or "CNF".
[0039] The term "micronized cellulose" refers to fibrous cellulose having a number average minor axis diameter in the range of 1 nm to 1000 nm. The fine cellulose 6 and the core particles 8 are bonded together and inseparably connected.
[0040] The method for forming the composite particles 4 is not particularly limited, but for example, an O / W Pickering emulsion is formed using the fine cellulose 6, and the droplets inside the emulsion are solidified to form solid core particles, thereby making it possible to obtain composite particles 4 in which the core particles 8 and the fine cellulose 6 are bound together and inseparable. By using the fine cellulose 6, it is possible to form droplets and form the composite particles 4 without using additives such as surfactants.
[0041] The term "inseparable" means that the micronized cellulose 6 and the core particles 8 do not separate and the coating state of the core particles 8 with the micronized cellulose 6 is maintained, even after, for example, a procedure of purifying and washing the composite particles 4 by centrifuging a dispersion liquid containing the composite particles 4 to remove the supernatant and then redispersing the composite particles 4 by adding a solvent, or after repeated washing with a solvent by filtration and washing using a membrane filter. The coating state can be confirmed, for example, by observing the surface of the composite particles 4 with a scanning electron microscope.
[0042] Regarding the bonding mechanism between the finely divided cellulose 6 and the core particles 8 in the composite particles 4, the composite particles 4 are produced using an O / W type emulsion stabilized by the finely divided cellulose 6 as a template, and therefore the droplets inside the emulsion solidify when they come into contact with the finely divided cellulose 6. Therefore, in the composite particles 4 obtained after solidification, it is expected that at least a portion of the finely divided cellulose 6 present on the surface of the core particles 8 will be incorporated into the interior of the core particles 8.
[0043] For the above reasons, it is presumed that the fine cellulose 6 is physically fixed to the core particles 8 after solidification, and that the core particles 8 and the fine cellulose 6 ultimately reach an inseparable state. Here, the O / W type emulsion is also called oil-in-water type, in which water is the continuous phase and oil is dispersed as oil droplets (oil particles).
[0044] In addition, since the composite particles 4 are produced using the O / W type emulsion stabilized by the fine cellulose 6 as a mold, the shape of the composite particles 4 is a true sphere derived from the O / W type emulsion. In detail, the coating layer 7 formed using the fine cellulose 6 is formed on the surface of the true spherical core particle 8 with a relatively uniform thickness. The average thickness of the coating layer 7 is calculated by, for example, cutting the composite particles 4 fixed with an embedding resin with a microtome, observing with a scanning electron microscope, measuring the thickness of the coating layer 7 in the cross-sectional image of the composite particles 4 in the image at 100 random points on the image, and taking the average value. In addition, the composite particles 4 are uniformly coated with the coating layer 7 with a relatively uniform thickness.
[0045] The coefficient of variation of the thickness of the coating layer 7 is preferably 0.5 or less, and more preferably 0.4 or less. When the coefficient of variation of the thickness of the coating layer 7 containing the micronized cellulose 6 exceeds 0.5, for example, recovery of the composite particles 4 may become difficult.
[0046] Furthermore, the fine cellulose 6 is preferably in a fibrous form derived from a microfibril structure. Specifically, the fine cellulose 6 is in a fibrous form, and preferably has a number average minor axis diameter in the range of 1 nm to 1000 nm, a number average major axis diameter of 50 nm or more, and further, the number average major axis diameter is 5 times or more the number average minor axis diameter. The crystal structure of the fine cellulose 6 is preferably cellulose type I.
[0047] (Method of manufacturing composite particles) FIG. 3 shows an example of a method for producing the composite particle 4. The method for producing the composite particle 4 includes a first composite particle step, a second composite particle step, and a third composite particle step. The first step of the composite particle production is a step of defibrating a cellulose raw material in a solvent to obtain a dispersion 10 of microfibrillated cellulose 6, as shown in FIG. 3(a).
[0048] The second composite particle process is a process in which at least a part of the surface of droplets 9 in a dispersion 10 of micronized cellulose 6 is covered with micronized cellulose 6 to stabilize the droplets 9 as an emulsion, as shown in FIG. 3(a).
[0049] The third composite particle process is a process in which, as shown in Figure 3(b), while at least a portion of the surface of the droplets 9 is covered with the micronized cellulose 6, the droplets 9 are solidified to form core particles 8, thereby covering at least a portion of the surface of the core particles 8 with the micronized cellulose 6 and making the core particles 8 and the micronized cellulose 6 inseparable.
[0050] The composite particles 4 produced by the above-mentioned production method are formed as a dispersion in a solvent. Furthermore, by removing the solvent, the composite particles 4 are formed as a dry solid. The method of removing the solvent is not particularly limited, and for example, the excess solvent can be removed by centrifugation or filtration, and further, the composite particles 4 can be formed as a dry solid by thermally drying the composite particles in an oven.
[0051] At this time, the formed dry solid is not in the form of a film or aggregate, but is formed as a finely textured powder. It is known that the reason why the dry solid is formed as a finely textured powder is that, when the solvent is removed from a dispersion of fine cellulose 6, the fine cellulose 6 is strongly aggregated and formed into a film. On the other hand, in the case of a dispersion containing composite particles 4, since the fine cellulose 6 is a spherical composite particle fixed to the surface, even when the solvent is removed, the fine cellulose 6 does not aggregate, but only contacts at points between the composite particles 4, so that the dry solid is considered to be obtained as a finely textured powder. In addition, since there is no aggregation between the composite particles 4, it is easy to disperse the composite particles 4 obtained as a dry powder in a solvent again, and even after redispersion, the dispersion stability derived from the fine cellulose 6 bonded to the surface of the composite particles 4 is exhibited. Each step will now be described in detail.
[0052] (Composite particle 1st step) In the first step of the composite particle production process, various cellulose raw materials are dispersed in a solvent to form a suspension. The concentration of the cellulose raw material in the suspension is preferably within the range of 0.1% or more and less than 10%. This is because if the concentration of the cellulose raw material in the suspension is less than 0.1%, the solvent will be excessive and productivity will tend to be impaired, which is undesirable, and if the concentration of the cellulose raw material in the suspension is 10% or more, the suspension will rapidly thicken as the cellulose raw material is defibrated, which tends to make uniform defibration processing difficult, which is undesirable.
[0053] The solvent used to prepare the suspension preferably contains 50% or more of water, because if the proportion of water in the suspension is less than 50%, the dispersion of the microfibrillated cellulose 6 tends to be hindered in the process of defibrating the cellulose raw material in the solvent to obtain a dispersion 10 of the microfibrillated cellulose 6.
[0054] In addition, a hydrophilic solvent is preferred as a solvent other than water. The hydrophilic solvent is not particularly limited, but for example, alcohols such as methanol, ethanol, isopropanol, and cyclic ethers such as tetrahydrofuran are preferred. If necessary, the pH of the suspension may be adjusted to increase the dispersibility of the cellulose and the resulting fine cellulose 6. Examples of the aqueous alkali solution used for adjusting the pH include organic alkalis such as an aqueous sodium hydroxide solution, an aqueous lithium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous ammonia solution, an aqueous tetramethylammonium hydroxide solution, an aqueous tetraethylammonium hydroxide solution, an aqueous tetrabutylammonium hydroxide solution, and an aqueous benzyltrimethylammonium hydroxide solution. An aqueous sodium hydroxide solution is preferred from the standpoint of cost and the like.
[0055] The suspension is then subjected to a physical fiberization process to reduce the size of the cellulose raw material. The method of physical defibration treatment is not particularly limited, but examples include mechanical treatments such as using a high-pressure homogenizer, an ultra-high-pressure homogenizer, a ball mill, a roll mill, a cutter mill, a planetary mill, a jet mill, an attritor, a grinder, a juicer mixer, a homomixer, an ultrasonic homogenizer, a nanogenizer, and underwater head-on collision.
[0056] By carrying out the physical defibration treatment, the cellulose in the suspension is pulverized, and it is possible to obtain a dispersion of cellulose (microfiberized cellulose 6) that has been pulverized to such an extent that at least one side of the structure is on the order of nanometers. In addition, it is possible to adjust the number average minor axis diameter and number average major axis diameter of the obtained microfiberized cellulose 6 by adjusting the time and number of times of the physical defibration treatment.
[0057] As described above, a dispersion of cellulose pulverized to such an extent that at least one side of the structure is on the order of nanometers (dispersion 10 of pulverized cellulose 6) is obtained. The obtained dispersion can be used as it is or after dilution, concentration, etc., as a stabilizer for O / W emulsions.
[0058] Usually, the fine cellulose 6 has a fibrous shape derived from a microfibril structure, and therefore the fine cellulose 6 preferably has a fibrous shape within the range shown below. That is, the shape of the fine cellulose 6 is preferably fibrous. In addition, the number average minor axis diameter of the fibrous fine cellulose 6 may be within the range of 1 [nm] to 1000 [nm] in the minor axis diameter, and preferably within the range of 2 nm [nm] to 500 nm [nm]. Here, if the number average minor axis diameter is less than 1 [nm], a highly crystalline rigid fine cellulose fiber structure is not obtained, and it tends to be difficult to stabilize the emulsion and to carry out a polymerization reaction using the emulsion as a template. On the other hand, if the number average minor axis diameter of the minor axis diameter exceeds 1000 [nm], the size becomes too large to stabilize the emulsion, and it tends to be difficult to control the size and shape of the obtained composite particle 4. In addition, the number average major axis diameter is not particularly limited, but is preferably 5 times or more the number average minor axis diameter. If the number average major axis diameter is less than 5 times the number average minor axis diameter, it tends to be difficult to adequately control the size and shape of the composite particles 4, which is undesirable.
[0059] The number average minor axis diameter of the fine cellulose fibers is determined, for example, by measuring the minor axis diameters (minimum diameters) of 100 fibers by observation with a transmission electron microscope and an atomic force microscope, and taking the average value thereof. On the other hand, the number average major axis diameter of the fine cellulose fibers is determined, for example, by measuring the major axis diameters (maximum diameters) of 100 fibers by observation with a transmission electron microscope and an atomic force microscope, and taking the average value thereof.
[0060] The type and crystal structure of cellulose that can be used as the raw material of the fine cellulose 6 are not particularly limited. Specifically, as the raw material formed using cellulose type I crystals, in addition to wood-based natural cellulose, non-wood-based natural cellulose such as cotton linter, bamboo, hemp, bagasse, kenaf, bacterial cellulose, sea squirt cellulose, and valonia cellulose can be used. In addition, regenerated cellulose represented by rayon fiber and cupra fiber formed using cellulose type II crystals can also be used. In view of ease of material procurement, it is preferable to use wood-based natural cellulose as the raw material. The wood-based natural cellulose is not particularly limited, and for example, it is possible to use those that are generally used in the production of cellulose nanofibers, such as softwood pulp, hardwood pulp, and waste paper pulp. Softwood pulp is preferable in view of ease of purification and fineness.
[0061] Furthermore, the fine cellulose raw material is preferably chemically modified. More specifically, it is preferable that an anionic functional group is introduced to the crystal surface of the fine cellulose raw material. This is because the introduction of the anionic functional group to the cellulose crystal surface makes it easier for the solvent to penetrate between the cellulose crystals due to the osmotic pressure effect, and the fine cellulose raw material is more easily refined.
[0062] The type and method of the anionic functional group to be introduced to the cellulose crystal surface are not particularly limited, but a carboxy group or a phosphate group is preferred, and a carboxy group is more preferred because of the ease of selective introduction to the cellulose crystal surface.
[0063] The method for introducing carboxyl groups to the fiber surface of cellulose is not particularly limited. Specifically, for example, carboxymethylation may be performed by reacting cellulose with monochloroacetic acid or sodium monochloroacetate in a high-concentration aqueous alkali solution. Alternatively, carboxyl groups may be introduced by directly reacting cellulose with a carboxylic anhydride compound such as maleic acid or phthalic acid gasified in an autoclave. Furthermore, a method using a co-oxidant in the presence of an N-oxyl compound such as TEMPO, which has high selectivity for the oxidation of alcoholic primary carbons, while maintaining the structure as much as possible under relatively mild aqueous conditions, may be used. Oxidation using an N-oxyl compound is more preferable for selectivity of the carboxyl group introduction site and reduction of environmental load.
[0064] Here, examples of the N-oxyl compound include TEMPO (2,2,6,6-tetramethylpiperidinyl-1-oxy radical), 2,2,6,6-tetramethyl-4-hydroxypiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine-N-oxyl, 4-ethoxy-2,2,6,6-tetramethylpiperidine-N-oxyl, and 4-acetamido-2,2,6,6-tetramethylpiperidine-N-oxyl. Among these, TEMPO, which has high reactivity, is preferred. The amount of the N-oxyl compound used may be the amount used as a catalyst, and is not particularly limited. Usually, the amount is within the range of 0.01% by mass or more and 5.0% by mass or less based on the solid content of the wood-based natural cellulose to be oxidized.
[0065] An example of an oxidation method using an N-oxyl compound is a method in which wood-based natural cellulose is dispersed in water and oxidized in the presence of an N-oxyl compound. In this case, it is preferable to use a co-oxidizing agent together with the N-oxyl compound. In this case, in the reaction system, the N-oxyl compound is sequentially oxidized by the co-oxidizing agent to generate an oxoammonium salt, and the cellulose is further oxidized by the oxoammonium salt. According to this oxidation treatment, the oxidation reaction proceeds smoothly even under mild conditions, and the introduction efficiency of the carboxyl group is improved. When the oxidation treatment is performed under mild conditions, the crystal structure of the cellulose is easily maintained.
[0066] As the co-oxidizing agent, any oxidizing agent can be used as long as it can promote the oxidation reaction, such as halogen, hypohalous acid, halo-ous acid, perhalogen acid, or their salts, halogen oxide, nitrogen oxide, peroxide, etc. Sodium hypochlorite is preferred in view of availability and reactivity. The amount of the co-oxidizing agent used is not particularly limited, and may be an amount capable of promoting the oxidation reaction. Usually, it is within the range of 1% by mass or more and 200% by mass or less based on the solid content of the wood-based natural cellulose to be oxidized.
[0067] In addition, at least one compound selected from the group formed by using bromides and iodides may be used in combination with the N-oxyl compound and the co-oxidizing agent. This allows the oxidation reaction to proceed smoothly, and improves the efficiency of introducing a carboxyl group. As such a compound, sodium bromide or lithium bromide is preferred, and sodium bromide is more preferred in terms of cost and stability. The amount of the compound used is not particularly limited, and may be an amount that can promote the oxidation reaction. Usually, it is within the range of 1% by mass or more and 50% by mass or less based on the solid content of the wood-based natural cellulose to be oxidized.
[0068] The reaction temperature of the oxidation reaction is preferably in the range of 4°C to 80°C, more preferably in the range of 10°C to 70°C. If the reaction temperature of the oxidation reaction is less than 4°C, the reactivity of the reagent tends to decrease and the reaction time tends to be longer. If the reaction temperature of the oxidation reaction is more than 80°C, side reactions are promoted, the cellulose sample is depolymerized, and the highly crystalline rigid fine cellulose fiber structure collapses, making it difficult to use the sample as a stabilizer for O / W emulsions.
[0069] The reaction time for the oxidation treatment can be appropriately set in consideration of the reaction temperature, the desired amount of carboxy groups, and the like, and is not particularly limited, but is usually about 10 minutes to 5 hours.
[0070] The pH of the reaction system during the oxidation reaction is not particularly limited, but is preferably 9 to 11. When the pH is 9 or more, the reaction can proceed efficiently. When the pH exceeds 11, a side reaction may proceed, which may accelerate the decomposition of the cellulose sample. In addition, in the oxidation treatment, as the oxidation proceeds, carboxyl groups are generated, which lowers the pH in the system, so that it is preferable to keep the pH of the reaction system at 9 to 11 during the oxidation treatment. As a method for keeping the pH of the reaction system at 9 to 11, for example, a method of adding an alkaline aqueous solution in response to a decrease in pH can be mentioned.
[0071] As the alkaline aqueous solution, for example, an organic alkali such as an aqueous sodium hydroxide solution, an aqueous lithium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous ammonia solution, an aqueous tetramethylammonium hydroxide solution, an aqueous tetraethylammonium hydroxide solution, an aqueous tetrabutylammonium hydroxide solution, an aqueous benzyltrimethylammonium hydroxide solution, etc. From the viewpoint of cost, etc., the aqueous alkaline solution is preferably an aqueous sodium hydroxide solution.
[0072] The oxidation reaction by the N-oxyl compound can be terminated, for example, by adding an alcohol to the reaction system. At this time, it is preferable to keep the pH of the reaction system within the range of 9 to 11. As the alcohol to be added to the reaction system, for example, in order to quickly terminate the reaction, low molecular weight alcohols such as methanol, ethanol, and propanol are preferable, and ethanol is particularly preferable in view of the safety of by-products generated by the reaction.
[0073] The reaction solution after the oxidation treatment may be directly subjected to the microparticulation step, but it is preferable to recover the oxidized cellulose contained in the reaction solution and wash it with a washing solution in order to remove catalysts such as N-oxyl compounds, impurities, etc. The recovery of the oxidized cellulose can be carried out by a known method such as filtration using a glass filter or a nylon mesh with a pore size of 20 μm. Pure water is preferable as the washing solution used to wash the oxidized cellulose.
[0074] In order to enhance the affinity between the produced fine cellulose 6 and the binder matrix 5, the carboxyl groups of the oxidized cellulose may be converted to quaternary alkylamines. To convert the carboxyl groups of oxidized cellulose to quaternary alkylamines, it is preferable to first acidify the carboxyl groups that have been alkalized when controlling the pH during the oxidation reaction by washing with an acid such as hydrochloric acid and then with distilled water.Then, the recovered oxidized cellulose is dispersed in distilled water or the like, and a quaternary alkyl ammonium salt is added.
[0075] Examples of the quaternary alkyl ammonium salt include, but are not limited to, monoalkyl trimethyl ammonium salt, dialkyl dimethyl ammonium salt, trialkyl monomethyl ammonium salt, alkyl benzyl dimethyl ammonium salt, and the like.
[0076] When the obtained TEMPO-oxidized cellulose is subjected to defibration treatment, cellulose nanofibers (CNF) with a uniform fiber width of about 3 nm are obtained. When CNF is used as the raw material for the micronized cellulose 6 of the composite particles 4, the particle size of the obtained O / W type emulsion tends to be uniform due to its uniform structure.
[0077] (Composite particle 2nd step) Specifically, the second composite particle process is a process in which at least one type of polymerizable monomer or polymer having no affinity is added to the dispersion liquid 10 obtained in the first composite particle process, and the at least one type of polymerizable monomer or polymer having no affinity is further dispersed in the dispersion liquid 10 as droplets 9, and then at least a portion of the surface of the droplets 9 is coated with micronized cellulose 6 to prepare an O / W type emulsion stabilized by the micronized cellulose 6.
[0078] Methods for preparing an O / W type emulsion include, for example, a method of emulsifying by adding a polymerizable monomer containing an initiator to the dispersion liquid 10, a method of dissolving a polymer that is solid at room temperature in a solvent that has low compatibility with the microfibrillated cellulose dispersion and adding the resulting solution to the dispersion liquid 10, and a method of adding a polymer that is solid at room temperature to the dispersion liquid 10 and heating the polymer to a temperature above the temperature at which it has fluidity to melt and emulsify. In any of these methods, it is preferable that the polymerizable monomer or polymer to be added is incompatible with the dispersion liquid 10. If there is compatibility, it becomes difficult to form polymer droplets in the dispersion liquid 10, and it tends to be difficult to obtain a complex.
[0079] The polymerizable monomer that can be used in the method of adding a mixture of a polymerizable monomer containing an initiator to the dispersion liquid 10 to form an emulsion is not particularly limited as long as it is a polymer monomer, has a polymerizable functional group in its structure, is liquid at room temperature, is completely incompatible with water, and can form a polymer (high molecular weight polymer) by a polymerization reaction. The polymerizable monomer has at least one polymerizable functional group. A polymerizable monomer having one polymerizable functional group is also called a monofunctional monomer. A polymerizable monomer having two or more polymerizable functional groups is also called a polyfunctional monomer. The type of polymerizable monomer is not particularly limited, but examples include (meth)acrylic monomers and vinyl monomers. In addition, it is also possible to use polymerizable monomers having a cyclic ether structure such as an epoxy group or an oxetane structure (for example, ε-caprolactone, etc.). The term "(meth)acrylate" includes both "acrylate" and "methacrylate".
[0080] Examples of monofunctional (meth)acrylic monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobornyl (meth)acrylate. acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, benzyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phosphate (meth)acrylate, ethylene oxide modified phosphate (meth)acrylate, phenoxy (meth)acrylate, ethylene oxide modified phenoxy (meth)acrylate, propylene oxide modified fluorine Phenoxy (meth)acrylate, nonylphenol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, propylene oxide modified nonylphenol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, diethyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hexahydrohydrogen phthalate, 2-(meth)acryloyloxypropyl tetrahydrohydrogen phthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate,adamantane derivative mono(meth)acrylates such as adamantyl acrylate having a monovalent mono(meth)acrylate derived from 2-adamantane and adamantanediol;
[0081] Examples of bifunctional (meth)acrylic monomers include di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and hydroxypivalic acid neopentyl glycol di(meth)acrylate.
[0082] Examples of the trifunctional or higher (meth)acrylic monomer include tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris(2-hydroxyethylisocyanurate tri(meth)acrylate, and glycerin tri(meth)acrylate; trifunctional (meth)acrylate compounds such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and ditrimethylolpropane tri(meth)acrylate. Examples of the (meth)acrylate include polyfunctional (meth)acrylate compounds having three or more functional groups, such as pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate, as well as polyfunctional (meth)acrylate compounds in which a portion of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone.
[0083] As the monofunctional vinyl monomer, for example, a liquid that is not compatible with water at room temperature such as vinyl ether, vinyl ester, aromatic vinyl, particularly styrene and styrene monomers, is preferable. In addition, as the monofunctional aromatic vinyl monomer, styrene, for example, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, isopropenyltoluene, isobutyltoluene, tert-butylstyrene, vinylnaphthalene, vinylbiphenyl, 1,1-diphenylethylene, etc. can be mentioned.
[0084] Examples of polyfunctional vinyl monomers include polyfunctional groups having unsaturated bonds such as divinylbenzene, and liquids that are incompatible with water at room temperature are preferred.Specific examples of polyfunctional vinyl monomers include divinylbenzene, 1,2,4-trivinylbenzene, 1,3,5-trivinylbenzene, and other divinyls, as well as tetramethylene bis(ethyl fumarate), hexamethylene bis(acrylamide), triallyl cyanurate, and triallyl isocyanurate.
[0085] Specific examples of styrene-based monomers include divinylbenzene, trivinylbenzene, divinyltoluene, divinylnaphthalene, divinylxylene, divinylbiphenyl, bis(vinylphenyl)methane, bis(vinylphenyl)ethane, bis(vinylphenyl)propane, and bis(vinylphenyl)butane.
[0086] In addition to these, polyether resins, polyester resins, polyurethane resins, epoxy resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiolpolyene resins, and the like having at least one polymerizable functional group can also be used, and the material is not particularly limited.
[0087] The polymerizable monomers may be used alone or in combination of two or more kinds.
[0088] The polymerizable monomer may contain a polymerization initiator in advance. Examples of common polymerization initiators include radical initiators such as organic peroxides and azo polymerization initiators.
[0089] Examples of organic peroxides include peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxycarbonates, and peroxyesters.
[0090] Examples of the azo polymerization initiator include ADVN and AIBN. For example, 2,2-azobis(isobutyronitrile) (AIBN), 2,2-azobis(2-methylbutyronitrile) (AMBN), 2,2-azobis(2,4-dimethylvaleronitrile) (ADVN), 1,1-azobis(1-cyclohexanecarbonitrile) (ACHN), dimethyl-2,2-azobisisobutyrate (MAIB), 4,4-azobis(4-cyanovaleric acid) (ACVA), 1,1-azobis(1-acetoxy-1-phenylethane), 2,2-azobis(2-methylbutyramide), 2,2-azobis(4 -methoxy-2,4-dimethylvaleronitrile), 2,2-azobis(2-methylamidinopropane) dihydrochloride, 2,2-azobis[2-(2-imidazolin-2-yl)propane], 2,2-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2-azobis(2,4,4-trimethylpentane), 2-cyano-2-propylazoformamide, 2,2-azobis(N-butyl-2-methylpropionamide), 2,2-azobis(N-cyclohexyl-2-methylpropionamide), and the like.
[0091] In the second composite particle process, by using a polymerizable monomer that already contains a polymerization initiator, when an O / W type emulsion is formed, the polymerizable monomer droplets 9 inside the emulsion particles contain the polymerization initiator, which makes it easier for the polymerization reaction to proceed when polymerizing the monomer inside the emulsion in the third composite particle process.
[0092] The weight ratio of the polymerizable monomer and the polymerization initiator that can be used in the second composite particle step is not particularly limited, but it is usually preferable that the polymerization initiator is 0.1 parts by mass or more per 100 parts by mass of the polymerizable monomer. If the polymerizable monomer is less than 0.1 parts by mass, the polymerization reaction does not proceed sufficiently, and the yield of the composite particle 4 tends to decrease, which is not preferable.
[0093] Examples of the polymer that can be used in the method of dissolving a polymer that is solid at room temperature in a solvent that is poorly compatible with the fine cellulose dispersion, adding the solution to the fine cellulose dispersion, and forming an yr emulsion include the polymer obtained by polymerizing the above-mentioned polymerizable monomer. In addition, as a solvent for dissolving a polymer that is solid at room temperature, a solvent that is poorly compatible with the fine cellulose dispersion is preferable. When the solubility in water is high, the solvent easily dissolves from the polymer phase to the water phase, so that emulsification tends to be difficult. When the solubility in water is not high, the solvent cannot move from the polymer phase, so that it tends to be very difficult to obtain composite particles. In addition, the solvent that dissolves the polymer preferably has a boiling point of 90 [°C] or less. When the boiling point is higher than 90 [°C], the fine cellulose dispersion tends to evaporate before the solvent that dissolves the polymer, so that it tends to be very difficult to obtain composite particles. Specific examples of the solvent that dissolves the polymer include dichloromethane, chloroform, 1,2-dichloroethane, and benzene.
[0094] Polymers that are solid at room temperature can be used in the method of adding a polymer that is solid at room temperature to a fine cellulose dispersion, heating the polymer to a temperature at which the polymer has fluidity or higher to melt the polymer, and emulsifying the polymer. The polymer that has fluidity is a melting point or glass transition temperature. The melting point or glass transition temperature of the polymer to be added is preferably within a range of 40°C to 90°C. When the melting point or glass transition temperature of the polymer is less than 40°C, it is difficult to solidify the polymer at room temperature, and it tends to be very difficult to obtain a composite. In addition, when the melting point or glass transition temperature of the polymer is 90°C or higher, water, which is a solvent of the fine cellulose dispersion heated together with the polymer, tends to evaporate rather than dissolving the polymer, making it difficult to emulsify the polymer. Therefore, specific examples of polymers that can be used in the present invention include poly-S-methylheptene, polydecene, polyvinyl palmitate, polyvinyl stearate, cis-1,4-polychloroprene, it cis-1,4-poly-1,3 pentadiene, it trans-1,4-poly-1,3 hexadiene, it trans-1,4-poly-1,3 heptadiene, it trans-1,4-poly-1,3 octadiene, polyhexamethylene oxide, polyoctamethylene oxide, polybutadiene oxide, polytetramethylene sulfide, polypentamethylene sulfide, polyhexamethylene sulfide, polymethylene thiotetramethylene sulfide, polyethylene thiotetramethylene sulfide, and polytrimethylene disulfide.
[0095] The weight ratio of the micronized cellulose dispersion and the polymer and the mixed solution of the polymer and the polymerizable monomer that can be used in the second composite particle step is not particularly limited, but it is preferable that the polymer and the mixed solution of the polymer and the polymerizable monomer are in the range of 1 part by mass to 50 parts by mass to 100 parts by mass of the micronized cellulose fiber. If the polymer and the mixed solution of the polymer and the polymerizable monomer is less than 1 part by mass, the yield of the composite particles 4 tends to decrease, which is not preferable. Also, if the polymer and the mixed solution of the polymer and the polymerizable monomer exceeds 50 parts by mass, it tends to be difficult to uniformly coat the droplets 9 with the micronized cellulose 6, which is not preferable.
[0096] The method for producing the O / W type emulsion is not particularly limited, but may be a general emulsification treatment, for example, various homogenizer treatments or mechanical stirring treatments, and specific examples of such mechanical treatments include high-pressure homogenizers, ultra-high-pressure homogenizers, universal homogenizers, ball mills, roll mills, cutter mills, planetary mills, jet mills, attritors, grinders, juicer mixers, homomixers, ultrasonic homogenizers, nanogenizers, underwater counter-collision, paint shakers, etc. A combination of multiple mechanical treatments may also be used.
[0097] For example, when an ultrasonic homogenizer is used, a polymerizable monomer is added to the dispersion liquid 10 obtained in the first composite particle process to prepare a mixed solvent, and the tip of the ultrasonic homogenizer is inserted into the mixed solvent to perform ultrasonic treatment. The treatment conditions for the ultrasonic homogenizer are not particularly limited, but for example, the frequency is generally 20 [kHz] or more, and the output is [10 W / cm 2 The treatment time is not particularly limited, but is usually about 10 seconds to 1 hour.
[0098] By ultrasonic treatment, droplets 9 are dispersed in dispersion liquid 10, and emulsification progresses, and further, micronized cellulose 1 is selectively adsorbed to the liquid / liquid interface between droplets 9 and dispersion liquid 10, so that droplets 9 are covered with micronized cellulose 6, forming a stable structure as an O / W type emulsion. Emulsions stabilized by the adsorption of solid matter to the liquid / liquid interface in this way are academically known as "Pickering emulsions."
[0099] As described above, the mechanism by which Pickering emulsions are formed by microfibrillated cellulose fibers is thought to be that cellulose exhibits amphiphilic properties due to the presence of hydrophilic sites derived from hydroxyl groups and hydrophobic sites derived from hydrocarbon groups in its molecular structure, and thus is adsorbed to the liquid / liquid interface between the hydrophobic monomer and the hydrophilic solvent due to its amphiphilic properties.
[0100] The O / W emulsion structure can be confirmed, for example, by observation with an optical microscope. The particle size of the O / W emulsion is not particularly limited, but is usually within the range of 0.1 μm to 1000 μm.
[0101] In the O / W emulsion structure, the thickness of the fine cellulose layer (coating layer 7) formed on the surface of the droplets 9 is not particularly limited, but is usually within the range of about 3 nm to 1000 nm. The thickness of the coating layer 7 can be measured, for example, by using a cryo-TEM.
[0102] (Composite particle 3rd step) Specifically, in the composite particle third step, when a method of adding a polymerizable monomer containing an initiator to the dispersion liquid 10 and emulsifying it is used in the composite particle second step, the method of polymerizing the polymerizable monomer is not particularly limited and can be appropriately selected depending on the type of polymerizable monomer and the type of polymerization initiator used. For example, a suspension polymerization method can be used as a method of polymerizing the polymerizable monomer.
[0103] The specific suspension polymerization method is not particularly limited, and can be carried out using a known method. For example, the droplets 9 containing the polymerization initiator and the polymerizable monomer, which are prepared in the second composite particle process, are covered with the fine cellulose 6, and the stabilized O / W type emulsion is heated while being stirred. The stirring method is not particularly limited, and a known method can be used, and specifically, a disperser or a stirrer can be used. Also, only the heating treatment may be performed without stirring. The temperature condition during heating can be appropriately set depending on the type of polymerizable monomer and the type of polymerization initiator, but is preferably within the range of 20 [°C] to 90 [°C]. If the heating temperature is less than 20 [°C], the polymerization reaction rate tends to decrease, which is not preferable, and if the heating temperature exceeds 90 [°C], the fine cellulose dispersion tends to evaporate, which is not preferable. The time for the polymerization reaction can be appropriately set depending on the type of polymerizable monomer and the type of polymerization initiator, but is usually about 1 hour to 24 hours. The polymerization reaction may be performed by irradiation with ultraviolet light, which is a type of electromagnetic wave. Moreover, instead of electromagnetic waves, particle beams such as electron beams may also be used.
[0104] In the second step of the composite particle production, when a method is used in which a polymer that is solid at room temperature is dissolved in a solvent that has low compatibility with the fine cellulose dispersion liquid and the solution is added to the fine cellulose dispersion liquid to form an emulsion, the polymer can be solidified by heating the emulsion and volatilizing the solvent that dissolved the polymer. The temperature conditions during heating can be appropriately set depending on the type of solvent to be dissolved, but it is preferable to set the temperature at or above the boiling point of the solvent and below 90 [°C]. If the heating temperature is lower than the boiling point of the solvent, the solvent will move slowly into the aqueous phase, and if the heating temperature exceeds 90 [°C], the fine cellulose dispersion liquid tends to evaporate, which is not preferable.
[0105] In the second composite particle process, when a method is used in which a polymer that is solid at room temperature is added to the dispersion liquid 10, and then the polymer is heated to a temperature above which it becomes fluid, thereby melting and emulsifying it, it is possible to solidify the polymer by cooling the emulsion to a temperature below which the polymer becomes fluid.
[0106] Immediately after the solidification reaction is completed, the dispersion of the composite particles 4 contains a large amount of water and free micronized cellulose 6 that has not contributed to the formation of the coating layer of the composite particles 4. Therefore, as shown in Fig. 3(c), the produced composite particles 4 need to be collected and purified.
[0107] As a method for recovering and purifying the prepared composite particles 4, washing by centrifugation or washing by filtration is preferable. As a method for washing by centrifugation, a known method can be used. Specifically, the composite particles 4 are precipitated by centrifugation, the supernatant is removed, and the composite particles 4 are redispersed in a water-methanol mixed solvent. Finally, the residual solvent is removed from the precipitate obtained by centrifugation to recover the composite particles 4. As for the filtration and washing, a known method can be used. For example, a PTFE membrane filter with a pore size of 0.1 [μm] is used to repeatedly perform suction filtration with water and methanol, and finally, the composite particles 4 can be recovered by further removing the residual solvent from the paste remaining on the membrane filter.
[0108] The method for removing the residual solvent is not particularly limited, and can be, for example, air drying or heat drying in an oven. The thus obtained dry solid material containing the composite particles 4 is obtained as a finely textured powder without being in the form of a film or aggregates, as described above.
[0109] Furthermore, the conversion of the finely divided cellulose 6 to a quaternary alkylamine does not have to be carried out before the production of the composite particles 4. Instead of carrying out the ammonium salt process as in the case of oxidized cellulose, the finely divided cellulose 6 may be used to produce the composite particles 4, and then the ammonium salt process may be carried out to convert the finely divided cellulose 6 to a quaternary alkylamine, which is to be coated on the composite particles 4.
[0110] <Binder Matrix> The binder matrix 5 is a layer that constitutes the surface protective layer 3, and is formed using the aqueous polyurethane resin composition (A).
[0111] (Aqueous polyurethane resin composition (A)) The aqueous polyurethane resin composition (A) is formed by blending the polyurethane resin water dispersion (B) and the polyisocyanate water dispersion (C) in such a manner that the solid content of the polyisocyanate water dispersion is 10 to 80 parts by mass per 100 parts by mass of the solid content of the polyurethane resin water dispersion.
[0112] In addition, the aqueous polyurethane resin composition (A) is blended so that the solid content of the polyisocyanate water dispersion is 10 to 80 parts by mass per 100 parts by mass of the solid content of the polyurethane resin water dispersion, and preferably so that the solid content of the polyisocyanate water dispersion is 20 to 60 parts by mass per 100 parts by mass of the solid content of the polyurethane resin water dispersion.
[0113] If the solid content of the polyisocyanate water dispersion is less than 10 parts by mass, there is a problem that the adhesion to substrates such as decorative boards, wallpapers, etc. is reduced. If the solid content of the polyisocyanate water dispersion is more than 80 parts by mass, there is a problem that the surface protective layer 3 formed from the aqueous polyurethane resin composition (A) becomes soft, and the blocking property is reduced when wound up after coating.
[0114] The solid content refers to the portion remaining after removing water from the polyurethane resin water dispersion and the polyisocyanate water dispersion. The aqueous polyurethane resin composition (A) may contain additives such as ultraviolet absorbers, pigments or dyes, water for adjusting viscosity, dispersion stabilizers, thixotropic agents, antioxidants, defoamers, thickeners, dispersants, surfactants, catalysts, fillers, lubricants, antistatic agents, hindered amine light stabilizers, and film-forming assistants.
[0115] (Polyurethane resin water dispersion (B)) The polyurethane resin aqueous dispersion (B) is an aqueous dispersion formed by emulsifying a urethane prepolymer obtained by reacting a polyester polyol (D) with an organic polyisocyanate (E). The polyurethane resin water dispersion (B) can be produced by a known method. For example, in addition to the one-shot method in which the polyester polyol (D) and the organic polyisocyanate (E) are added at once to react, the organic polyisocyanate (E) is reacted with a part of an active hydrogen compound to form a prepolymer having an isocyanate group at the end, and then the remaining part of the active hydrogen compound is added and further reacted to produce the polyurethane resin water dispersion. Alternatively, the polyurethane resin water dispersion may be produced by reacting the organic polyisocyanate (E) with the above-mentioned method in an inert organic solvent compatible with water, adding water after the reaction, and removing the organic solvent.
[0116] In addition, emulsification may be performed by using a suitable surfactant in combination, for example, an anionic surfactant represented by higher fatty acids, resin acids, acidic fatty alcohols, sulfuric acid esters, higher alkyl sulfonic acids, alkylaryl sulfonic acids, sulfonated castor oil, sulfosuccinic acid esters, etc., or a nonionic surfactant represented by a known reaction product of ethylene oxide with a long-chain fatty alcohol or a phenol.
[0117] The production of the urethane prepolymer is carried out using polyester polyol (D) and organic polyisocyanate (E) at a temperature usually in the range of 20°C to 140°C, preferably in the range of 40°C to 120°C. In order to promote the reaction, a catalyst used in a normal urethane reaction may be used, if necessary. Examples of the urethane reaction catalyst include amine catalysts (e.g., triethylamine, N-ethylmorpholine, triethylenediamine, etc.), tin catalysts (e.g., dibutyltin dilaurate, dioctyltin dilaurate, tin octylate, etc.), and titanium catalysts (e.g., tetrabutyl titanate, etc.).
[0118] The amount of the catalyst used is usually 0.1% by mass or less in the urethane prepolymer.
[0119] Examples of organic solvents that are inert to the organic polyisocyanate (E) and compatible with water include ester solvents (e.g., ethyl acetate, butyl acetate, ethyl cellosolve acetate, etc.), ketone solvents (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.), ether solvents (e.g., dioxane, tetrahydrofuran, propylene glycol dimethyl ether, etc.), and amide solvents (e.g., dimethylformamide, N-methylpyrrolidone, etc.). These solvents can be used alone or in combination of two or more.
[0120] Of these, ethyl acetate, methyl ethyl ketone, acetone, and tetrahydrofuran are preferred.
[0121] (Polyisocyanate Water Dispersion (C)) The polyisocyanate aqueous dispersion (C) can form a crosslinked product by condensation of the isocyanate groups contained in the dispersion with the hydroxyl groups, etc., of the polyurethane resin aqueous dispersion (B), thereby producing a protective film.
[0122] Examples of the polyisocyanate aqueous dispersion (C) include an isocyanurate modified product of hexamethylene diisocyanate (trade name: AQUANATE 100, AQUANATE 200, manufactured by Nippon Polyurethane Industry Co., Ltd., or trade name: Baydur 310, manufactured by Sumitomo Bayer Urethane Co., Ltd.), an adduct modified product of hexamethylene diisocyanate (trade name: Duranate WB40-80D, manufactured by Asahi Chemical Industry Co., Ltd.), and the like.
[0123] (Polyester polyol (D)) Examples of aromatic dicarboxylic acids that are the acid components constituting the polyester polyol (D) include isophthalic acid, terephthalic acid, orthophthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyldicarboxylic acid, tetrahydrophthalic acid, etc., or reactive derivatives thereof such as acid anhydrides, alkyl esters, acid halides, etc. These aromatic dicarboxylic acids can be used alone or in combination of two or more kinds.
[0124] Examples of the alicyclic dicarboxylic acid of the acid component constituting the polyester polyol (D) include hydrides of the aromatic dicarboxylic acids, or reactive derivatives thereof such as acid anhydrides, alkyl esters, acid halides, etc. These alicyclic dicarboxylic acids can be used alone or in combination of two or more.
[0125] Examples of other acid components constituting the polyester polyol (D) include aliphatic dicarboxylic acids such as malonic acid, succinic acid, tartaric acid, oxalic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, alkylsuccinic acid, linoleic acid, maleic acid, fumaric acid, mesaconic acid, citraconic acid, and itaconic acid, or reactive derivatives thereof such as acid anhydrides, alkyl esters, and acid halides. These aliphatic dicarboxylic acids can be used alone or in combination of two or more.
[0126] The polyester polyol (D) contains at least one of an aromatic dicarboxylic acid and an alicyclic dicarboxylic acid as an acid component in an amount of 35 mass % or more.
[0127] If the content of at least one of the aromatic dicarboxylic acid and the alicyclic dicarboxylic acid is less than 35% by mass, the surface protective layer 3 becomes soft, and there is a risk of blocking occurring when the decorative sheet 1 is wound up.
[0128] As the aromatic dicarboxylic acid, isophthalic acid, terephthalic acid, orthophthalic acid, etc. are preferred. As the alicyclic dicarboxylic acid, cyclohexanedicarboxylic acid and the like are preferable. The aromatic dicarboxylic acid and the alicyclic dicarboxylic acid may be used alone or in combination.
[0129] Examples of glycol components constituting the polyester polyol (D) include linear glycols such as ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexamethylene glycol, and diethylene glycol, and branched glycols such as 1,2-propylene glycol, 1-methyl-1,3-butylene glycol, 2-methyl-1,3-butylene glycol, neopentyl glycol, 1-methyl-1,4-pentanediol, 2-methyl-1,4-pentanediol, 1,2-dimethyl-neopentyl glycol, 2,3-dimethyl-neopentyl glycol, 1-methyl-1,5-pentanediol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,2-dimethylbutylene glycol, 1,3-dimethylbutylene glycol, 2,3-dimethylbutylene glycol, and 1,4-dimethylbutylene glycol. These linear or branched glycols can be used alone or in combination of two or more kinds.
[0130] The polyester polyol (D) can be obtained by dehydration condensation of an acid component and a glycol component in the same manner as in known polyester production methods.
[0131] The number average molecular weight of the polyester polyol (D) is within the range of 500 or more and 5,000 or less, preferably within the range of 1,000 or more and 4,000 or less, and more preferably within the range of 1,500 or more and 3,000 or less.
[0132] If the number average molecular weight is less than 500, the surface protective layer 3 formed from the aqueous polyurethane resin composition becomes hard and brittle, and the adhesion decreases. If the number average molecular weight exceeds 5,000, the surface protective layer 3 formed from the aqueous polyurethane resin composition becomes soft, and the blocking property decreases.
[0133] (Organic polyisocyanate (E)) The organic polyisocyanate (E) can include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, and araliphatic polyisocyanates.
[0134] Examples of aliphatic polyisocyanates include tetramethylene diisocyanate, dodecamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2-methylpentane-1,5-diisocyanate, and 3-methylpentane-1,5-diisocyanate.
[0135] Examples of the alicyclic polyisocyanate include isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, and 1,3-bis(isocyanatemethyl)cyclohexane.
[0136] Examples of aromatic polyisocyanates include tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 4,4'-dibenzyl diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, 1,3-phenylene diisocyanate, and 1,4-phenylene diisocyanate.
[0137] Examples of the aralkyldiphenylmethane diisocyanate include dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, α,α,α,α-tetramethylxylylene diisocyanate, and the like.
[0138] Examples of the organic polyisocyanate (E) include modified products such as dimers, trimers, and biuretized isocyanates of these organic polyisocyanates. These can be used alone or in combination of two or more kinds.
[0139] From the viewpoint of weather resistance, the organic polyisocyanate (E) is preferably an alicyclic polyisocyanate, specifically, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, etc. are preferred.
[0140] The organic polyisocyanate is contained in the urethane prepolymer in an amount of preferably 30% by mass or more and 50% by mass or less, more preferably 33% by mass or more and 45% by mass or less, and particularly preferably 37% by mass or more and 45% by mass or less.
[0141] If the content of the organic polyisocyanate is less than 30% by mass, there is a problem that blocking properties are reduced. On the other hand, if the content of the organic polyisocyanate is more than 50% by mass, the film-forming temperature during coating becomes too high, making it difficult to form a film. In addition, there is a problem that the film loses flexibility and the scratch resistance is reduced.
[0142] (effect) The decorative sheet 1 according to the first embodiment is made of an environmentally friendly material and has high hardness.
[0143] Furthermore, in the case of the decorative sheet 1 of the first embodiment, the surface protection layer 3 is formed using composite particles 4 and a binder matrix 5, whereby fine irregularities are formed on the surface of the surface protection layer 3, thereby making it possible to improve the blocking resistance of the surface protection layer 3.
[0144] <Modification> The decorative sheet 1 of the present invention is not limited in its layer structure. That is, it may be configured such that the surface protective layer 3 is disposed on the outermost surface of the decorative sheet 1. For example, although not shown, it may be configured such that a pattern layer, an adhesive layer, a transparent resin layer, and the surface protective layer 3 are laminated on the base sheet 2.
[0145] The design layer, adhesive layer, transparent resin layer and surface protective layer 3 are formed by, for example, printing such as gravure printing, flexographic printing, silk screen printing, offset printing, transfer printing, etc., applying a coating liquid with a spray, roller, brush, etc., laminating sheets, etc. In particular, it is preferable that the design layer, adhesive layer, transparent resin layer and surface protective layer 3 are each formed by a coating film made of an aqueous composition.
[0146] The thicknesses of the pattern layer, adhesive layer, transparent resin layer and surface protection layer 3 are not limited and can be appropriately determined depending on the application, characteristics, etc. of the final product. Usually, they are within the range of 0.1 μm to 500 μm.
[0147] (adhesive layer) The adhesive layer is present between the pattern layer and the transparent resin layer. The adhesive used in the adhesive layer can be appropriately selected depending on the components constituting the pattern layer or the transparent resin layer. For example, various adhesives including polyurethane resins, polyacrylic resins, polycarbonate resins, epoxy resins, etc. can be used. In addition to reactive curing types, adhesives such as hot melt types, ionizing radiation curing types, and ultraviolet curing types can also be used.
[0148] In the present invention, it is also possible to use a thermocompression adhesive and laminate the design layer and the transparent resin layer by thermocompression bonding.
[0149] In addition, the adhesive layer is desirably formed from an aqueous composition, since this can reduce the VOC of the decorative sheet 1. As the aqueous composition, a composition containing an aqueous binder can be used. The aqueous binder may be in any form, such as an aqueous resin solution or an aqueous resin emulsion. The resin used in these compositions can be the same as the aqueous binder of the aqueous composition used to form the design layer.
[0150] The method for applying the adhesive layer is not limited, and for example, methods such as roll coating, curtain flow coating, wire bar coating, reverse coating, gravure coating, gravure reverse coating, air knife coating, kiss coating, blade coating, smooth coating, comma coating, spray coating, flow coating, and brush coating can be used.
[0151] In the present invention, if necessary, the bonding surface may be subjected to a known adhesion enhancing treatment such as a corona discharge treatment, a plasma treatment, a degreasing treatment, or a surface roughening treatment.
[0152] The thickness of the adhesive layer varies depending on the transparent protective layer, the type of adhesive used, etc., but is generally preferably in the range of 0.5 μm to 30 μm, and more preferably in the range of 1 μm to 5 μm.
[0153] (Transparent resin layer) The transparent resin layer may be colored as long as it is transparent, and may be semi-transparent to the extent that the design layer is visible.
[0154] Examples of the resin forming the transparent resin layer include polyvinyl chloride, polyethylene terephthalate, polybutylene terephthalate, polyamide, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, ionomer, polymethylpentene, acrylic acid ester, methacrylic acid ester, polycarbonate, and cellulose triacetate. The resin forming the transparent resin layer is preferably a polyolefin resin such as polypropylene. More preferably, it is a polyolefin resin having stereoregularity. When using a polyolefin resin, it is preferable to form the transparent resin layer by extrusion of a molten polyolefin resin.
[0155] The transparent resin layer may contain various additives, such as a filler, a matting agent, a foaming agent, a flame retardant, a lubricant, an antistatic agent, an antioxidant, an ultraviolet absorber, a light stabilizer, a radical scavenger, and a soft component (e.g., rubber), as necessary.
[0156] The thickness of the transparent resin layer is not particularly limited, but may generally be within the range of 10 μm to 150 μm.
[0157] <Example> The present invention will be described in detail below with reference to examples, but the technical scope of the present invention is not limited to these examples. In each of the following examples, "%" indicates mass % (w / w%) unless otherwise specified.
[0158] Example 1 (Preparation of oxidized cellulose) As the cellulose, commonly available bleached softwood pulp was used. 60[g] of cellulose (calculated as bone dry mass) was added to 1000[g] of distilled water, stirred, swollen, and then defibrated in a mixer. 2200[g] of distilled water, 0.6[g] of TEMPO dissolved in 400[g] of distilled water, and a solution of 6[g] of sodium bromide were added, and 172[g] of sodium hypochlorite solution with a concentration of 2[mol / L] was added dropwise to start the oxidation reaction. The reaction temperature was always kept below 20[℃]. During the reaction, the pH in the system decreased, but 0.5[N] NaOH solution was added successively to adjust the pH to 10. The reaction was continued while monitoring the amount of NaOH solution added, and after 4 hours of reaction, 60[g] of ethanol was added to stop the reaction. 0.5[N] HCl was then added dropwise to the reaction solution to reduce the mpH to 1.8. Next, the reaction liquid was filtered using a nylon mesh, and the solids were further washed several times with water to remove the reaction reagents and by-products, yielding oxidized cellulose containing water with a solid concentration of 7%.
[0159] (Measurement of the amount of functional groups introduced) 0.2 g of wet oxidized cellulose was weighed out in a beaker, and distilled water was added to make up to 60 g. 0.5 mL of 0.1 M NaCl solution was added, and the pH was adjusted to 1.8 with 0.5 M hydrochloric acid. Then, 0.5 M NaOH solution was added dropwise and the conductivity was measured. The measurement was continued until the pH reached about 11. The part corresponding to the neutralization stage of the weak acid represents the carboxyl group content, and the amount of NaOH added was read from the conductivity curve, revealing that the carboxyl group content was 2.0 mmol / g.
[0160] Next, 20 mL of 0.5 M acetic acid, 60 mL of distilled water, and 1.8 g of sodium chlorite were added to 2 g of wet oxidized cellulose (calculated as bone dry mass), and the pH was adjusted to 4 and allowed to react for 48 hours. After this, the carboxyl group content was measured using the same method as above, and was found to be 2.1 mmol / g. From this, the aldehyde group content was calculated to be 0.1 mmol / g.
[0161] (Preparation of Micronized Cellulose Dispersion) Distilled water and 10 wt% tetraethylammonium hydroxide (TEAH, Kanto Chemical) were added to 57.14 g of oxidized cellulose (solid content 4 g) with a solid content of 7% prepared by the above-mentioned process to prepare 400 g of oxidized cellulose suspension with a pH of 10. The prepared suspension was treated for 60 minutes in a mixer with a rotating blade to obtain a microfibrillated cellulose dispersion. 10 g of the obtained microfibrillated cellulose dispersion was weighed out, to which 9.95 g of acetone and 0.05 g of distilled water were added and stirred to prepare a microfibrillated cellulose dispersion with a solid content of 0.5%.
[0162] (Process for preparing O / W type emulsion) Next, 1 g of 2,2-azobis-2,4-dimethylvaleronitrile (hereinafter also referred to as ADVN), a polymerization initiator, was dissolved in 10 g of divinylbenzene (hereinafter sometimes referred to as DVB), a polymerizable monomer. When the entire amount of the DVB / ADVN mixed solution was added to 40 g of a fine cellulose dispersion with a fine cellulose concentration of 0.5%, the DVB / ADVN mixed solution and the fine cellulose dispersion each separated into two highly transparent layers.
[0163] Next, the shaft of an ultrasonic homogenizer was inserted from the liquid surface of the upper layer of the mixture separated into two layers, and ultrasonic homogenization was performed for 3 minutes under the conditions of a frequency of 24 [kHz] and an output of 400 [W]. The appearance of the mixture after ultrasonic homogenization was a cloudy emulsion. Then, a drop of the mixture was dropped onto a slide glass, sealed with a cover glass, and observed under an optical microscope. It was confirmed that countless emulsion droplets of about 1 [μm] to several [μm] were generated and the dispersion was stabilized as an O / W type emulsion.
[0164] (Step of obtaining composite particles 4 coated with CNF by polymerization reaction) The O / W emulsion dispersion was placed in a water bath at 70°C and stirred with a stirrer for 8 hours to carry out the polymerization reaction. After 8 hours of treatment, the O / W emulsion dispersion was cooled to room temperature. There was no change in the appearance of the dispersion before and after the polymerization reaction. The obtained dispersion was centrifuged for 5 minutes at 75,000G (G is the acceleration of gravity), and a precipitate was obtained. The supernatant was removed by decantation to collect the precipitate, which was then washed repeatedly with pure water and methanol using a PTFE membrane filter with a pore size of 0.1μm. The purified and collected material thus obtained was redispersed at a concentration of 1%, and the particle size was evaluated using a particle size distribution analyzer (Nikkiso Co., Ltd.: NANOTRAC UPA-EX150), and the average particle size was 2.1μm. The purified and collected material was then air-dried and then vacuum-dried at room temperature (25°C) for 24 hours, yielding a finely textured dry powder (composite particle 4).
[0165] (Shape observation using a scanning electron microscope) The results of observing the obtained dry powder with a scanning electron microscope are shown in Figures 4 and 5. As shown in Figure 4, it was confirmed that by carrying out the polymerization reaction using the O / W emulsion droplets as a template, countless spherical composite particles were formed, which were derived from the shape of the emulsion droplets.
[0166] Furthermore, it was confirmed that the surface of the composite particles was uniformly covered with CNFs having a width of several nm, as shown in Figure 5. In addition, despite repeated washing by filtration and washing, the surface of the composite particles was equally and uniformly covered with fine cellulose, which indicates that in the present invention, the core particle inside the composite particle and the CNF, which is fine cellulose, may be bonded, and the core particle and the fine cellulose are in an inseparable state.
[0167] (Method of Preparing Binder Matrix) (Method for measuring hydroxyl value) The hydroxyl value was measured in accordance with "JIS K1557-1970." (number average molecular weight) The number average molecular weight was calculated from the hydroxyl value. (Acid value) The acid value was determined in accordance with "JIS K0070-1992" from the number of milligrams of KOH required to neutralize the free carboxyl groups contained in 1 [g] of solid content of the aqueous polyurethane resin composition.
[0168] (Synthesis of polyester glycol A) Terephthalic acid (210 parts by mass) and adipic acid (93 parts by mass) as acid components, and ethylene glycol (62 parts by mass) and neopentyl glycol (104 parts by mass) as glycol components were charged into a flask equipped with a dehydration device, and tetraisopropyl titanate (0.1 parts by mass) was added as a reaction catalyst, after which a condensation reaction was carried out at 220°C until the acid value was 1.0 or less and the moisture content was 0.05% or less.
[0169] The obtained polyester glycol A had a number average molecular weight of 2000, a hydroxyl value of 56 [mgKOH / g], and an acid content of 69 mass %.
[0170] Polyester glycol A (512.5 parts by mass), trimethylolpropane (13.3 parts by mass), dimethylolpropionic acid (24.7 parts by mass), cyclohexanedimethanol (73.9 parts by mass), dicyclohexylmethane diisocyanate (375.6 parts by mass), and methyl ethyl ketone (800 parts by mass) were added to a four-neck flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, and the mixture was allowed to react at 75°C for 4 hours to obtain a methyl ethyl ketone solution of a urethane prepolymer having a free isocyanate group content of 2.9% relative to the non-volatile content.
[0171] Then, the methyl ethyl ketone solution was cooled to 40[℃], and 15 parts by mass of "Nonionic surfactant Noigen EA-157" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., 30 parts by mass of "Tinuvin 900" manufactured by Ciba Specialty Chemicals Co., Ltd., and 20 parts by mass of "Tinuvin 123" manufactured by Ciba Specialty Chemicals Co., Ltd. were dissolved in methyl ethyl ketone (300 parts by mass) and added, and 23.6 parts by mass of 10% aqueous caustic soda solution was added to neutralize, and then 2200 parts by mass of water was gradually added and emulsified and dispersed using a homogenizer. Furthermore, 24.7 parts by mass of dipropylenetriamine was added and stirred for 1 hour. After that, the pressure was reduced and the solvent was removed in an environment of 50[℃], and a polyurethane water dispersion with a non-volatile content of about 35[%] was obtained.
[0172] Furthermore, 1,286 parts by mass of the polyurethane resin water dispersion (corresponding to 100 parts by mass of solid content (containing 186 parts by mass of water)) obtained in the above-mentioned synthesis example and a polyisocyanate water dispersion (using Aquanate 200: corresponding to 28.6 parts by mass of solid content) were dispersed in 28.6 parts by mass of water to prepare a coating liquid (total amount of water: 214.6 parts by mass).
[0173] (Adjustment of decorative sheet coating liquid) The above-mentioned dried composite particles were mixed with ethanol to prepare a composite particle dispersion liquid so that the amount of composite particles was 10 parts by mass. The composite particle dispersion liquid and the polyurethane resin in the coating liquid were adjusted so that the solid content weight ratio was 10:100 to prepare a coating liquid for forming a decorative sheet.
[0174] (Making decorative sheets) The coating solution for forming the decorative sheet was applied to the corona discharge treated surface of a 100 μm thick stretched polypropylene film (OPP) using a bar coater, and then dried in a dryer at 100°C for 30 seconds. After that, a coating film with a thickness of 3 μm was formed after drying, and the decorative sheet was produced. The prepared decorative sheets were used as test pieces to carry out an OPP adhesion test, a stain resistance test, a blocking test, and a weather resistance test.
[0175] Example 2 A decorative sheet of Example 2 was produced under the same conditions as in Example 1, except that the composite particle dispersion and the polyurethane resin were adjusted so that the solids weight ratio was 5:100.
[0176] Example 3 The decorative sheet of Example 3 was produced under the same conditions as Example 1, except that diethylene glycol diacrylate (Hitachi Chemical: product name FA-222A. In the following explanation, this may be referred to as "FA-222A") was used instead of DVB.
[0177] Example 4 As a polymer for forming the core particles, 6 g of polystyrene (hereinafter, may be referred to as "PS") was dissolved in 4 g of dichloromethane (boiling point: 39.6°C). Next, the entire amount of the mixed solution of PS and dichloromethane was added to 40 g of the fine cellulose dispersion liquid used in Example 1.
[0178] Next, the mixture was subjected to ultrasonic homogenization for 3 minutes under the conditions of a frequency of 24 [kHz] and an output of 400 [W], as in Example 1, to obtain an O / W type emulsion dispersion.
[0179] The O / W emulsion dispersion was then placed in a water bath at 70°C and stirred with a stirrer for 8 hours to volatilize the dichloromethane. After 8 hours of treatment, the dispersion was treated in the same manner as in Example 1 to obtain a dry powder (composite particles).
[0180] The obtained composite particles were mixed with ethanol to prepare a composite particle dispersion liquid so that the amount of the composite particles was 10 parts by mass. Using the prepared composite particle dispersion liquid, a decorative sheet of Example 4 was produced under the same conditions as Example 1.
[0181] Comparative Example 1 A decorative sheet of Comparative Example 1 was produced under the same conditions as in Example 1, except that the composite particle dispersion and the polyurethane resin were adjusted so that the solids weight ratio was 0.5:100.
[0182] Comparative Example 2 A decorative sheet of Comparative Example 2 was produced under the same conditions as in Example 1, except that the composite particle dispersion and the polyurethane resin were adjusted so that the solids weight ratio was 100:100.
[0183] Comparative Example 3 A decorative sheet of Comparative Example 3 was produced under the same conditions as in Example 1, except that commercially available polystyrene particles (Corefront: "Estapol") were used instead of composite particles.
[0184] The compositions of the decorative sheet coating solutions prepared in Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 1.
[0185] [Table 1]
[0186] The decorative sheets of Examples 1 to 4 and Comparative Examples 1 to 4 were subjected to the following measurements and evaluations. (Testing and Evaluation Methods) (1) OPP adhesion test: The test piece on which the coating was formed was aged at 25[℃] for 3 days, and the surface of the test piece was cut with a cutter knife to a width of 1[mm] to create 100 grids. Then, adhesive tape (Nichiban: Cellotape (registered trademark)) was applied to the test piece, and the applied adhesive tape was quickly peeled off.
[0187] The evaluation criteria for the OPP adhesion test are shown below. ◎: The coating did not peel off at all. ○: 80-99% of the coating remains △: 50-79% of the coating remains ×: Less than 50% of the coating remained
[0188] (2) Stain resistance test: The surface of the test piece was painted over with blue ink (water-based) and black pen (oil-based) to a diameter of 2 cm, left for 4 hours, wiped off with ethanol, and the surface was observed.
[0189] The evaluation criteria for the stain resistance test are shown below. ○: No stains were observed △: A little dirt remained ×: Significant stains remain
[0190] (3) Blocking test: The coated surfaces of the test pieces before the coating film hardens are pressed against each other with a pressure of 2.0 kg / cm 2 The coated surfaces were then removed after 24 hours and the state of blocking was observed.
[0191] The evaluation criteria for the blocking test are as follows. ○: Peeled off easily △: Peeled off with some resistance ×: Not peeled off
[0192] (4) Weather resistance test: The test pieces were exposed to UV light for 192 hours using an Iwasaki Electric Eye Super UV Tester, and then the appearance was visually evaluated. The exposure conditions were: temperature 63°C, humidity 50% RH, irradiation intensity 60mw / m 2 In addition, the exposure time was 20 hours and 4 hours of condensation per cycle, for a total of 8 cycles.
[0193] The evaluation criteria for the weather resistance test are shown below. ◎: No change was observed ○: A slight change in gloss was observed that did not affect the product characteristics. △: Slight whitening that affects product properties was observed. ×: Significant whitening was observed
[0194] (5) Pencil hardness test: The pencil hardness of the test pieces was measured in accordance with JIS K5600-5-4 using a Clemens scratch hardness tester manufactured by Tester Sangyo Co., Ltd.
[0195] In the pencil hardness test, the highest pencil hardness that did not cause scratches was recorded as the evaluation result.
[0196] The evaluation results of the decorative sheets produced in Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 2.
[0197] [Table 2]
[0198] As shown in Table 2, it was confirmed that the decorative sheets of Examples 1 to 4 had good blocking resistance and high pencil hardness.
[0199] On the other hand, it was confirmed that the decorative sheet of Comparative Example 1 had low blocking resistance. Also, it was confirmed that the decorative sheet of Comparative Example 2 turned white overall and had low stain resistance. Also, it was confirmed that the decorative sheet of Comparative Example 3 had low pencil hardness. [Explanation of symbols]
[0200] Reference Signs List 1: decorative sheet, 2: base sheet, 3: surface protective layer, 4: composite particle, 5: binder matrix, 6: fine cellulose, 7: coating layer, 8: core particle, 9: droplet, 10: dispersion medium
Claims
1. A surface protective layer including an aqueous polyurethane resin composition and composite particles is provided. The composite particles have a coating layer made of fine cellulose, a core particle including at least one type of polymer is disposed on a surface of the pulverized cellulose; the core particles are solid particles obtained by solidifying droplets inside an O / W type Pickering emulsion formed using the fine cellulose, The composite particles are particles in which the core particles and the micronized cellulose are bound to each other in an inseparable state, The inseparable state refers to a state in which, by centrifuging a dispersion liquid containing the composite particles to remove the supernatant, and then adding a solvent to redisperse the composite particles, the microfibrillated cellulose and the core particles do not separate, the core particles are kept coated with the microfibrillated cellulose, and the core particles are disposed on the surfaces of the microfibrillated cellulose. a layer constituting the surface protective layer is a binder matrix formed using an aqueous polyurethane resin composition, The aqueous polyurethane resin composition is formed by blending a polyurethane resin water dispersion and a polyisocyanate water dispersion, The polyurethane resin aqueous dispersion is an aqueous dispersion formed by emulsifying a urethane prepolymer obtained by reacting a polyester polyol with an organic polyisocyanate, A decorative sheet characterized in that the number average molecular weight of the polyester polyol is within the range of 500 or more and 5,000 or less.
2. A surface protective layer including an aqueous polyurethane resin composition and composite particles is provided. The composite particles have a coating layer made of fine cellulose, a core particle including at least one type of polymer is disposed on a surface of the pulverized cellulose; the core particles are solid particles obtained by solidifying droplets inside an O / W type Pickering emulsion formed using the fine cellulose, The composite particles are particles in which the core particles and the micronized cellulose are bound to each other in an inseparable state, The inseparable state refers to a state in which, by centrifuging a dispersion liquid containing the composite particles to remove the supernatant, and then adding a solvent to redisperse the composite particles, the microfibrillated cellulose and the core particles do not separate, the core particles are kept coated with the microfibrillated cellulose, and the core particles are disposed on the surfaces of the microfibrillated cellulose. a layer constituting the surface protective layer is a binder matrix formed using an aqueous polyurethane resin composition, The aqueous polyurethane resin composition is formed by blending a polyurethane resin water dispersion and a polyisocyanate water dispersion, The polyurethane resin aqueous dispersion is an aqueous dispersion formed by emulsifying a urethane prepolymer obtained by reacting a polyester polyol with an organic polyisocyanate, A decorative sheet, characterized in that the organic polyisocyanate is contained in the urethane prepolymer in an amount within the range of 30% by mass to 50% by mass.
3. 3. The decorative sheet according to claim 1, wherein the finely divided cellulose is converted into a quaternary alkylamine.
4. 4. The decorative sheet according to claim 1, wherein the surface of said surface protective layer has a pencil hardness of 2H or more according to a pencil hardness evaluation method.
5. 5. The decorative sheet according to claim 1, further comprising a base sheet on which said surface protective layer is laminated.
6. a decorative layer laminated on one surface of the base sheet; an adhesive layer laminated on a surface of the decorative layer opposite to the surface facing the base sheet; A transparent resin layer is laminated on the surface of the adhesive layer opposite to the surface facing the decorative layer, 6. The decorative sheet according to claim 5, wherein said surface protective layer is laminated on the surface of said transparent resin layer opposite to the surface facing said adhesive layer.
7. 7. The decorative sheet according to claim 5, wherein the base sheet contains a polyolefin resin as a resin component.
Citation Information
Patent Citations
Water-based topcoat varnish for architectural finish material having cellophane tape strippability and decorative sheet using the same
JP1997158098A
Decorative sheet
JP1999198309A
Aqueous acrylic-urethane copolymer composition and its use
JP2000119362A
Decorative sheet
JP2007118584A
Sheet for building material using aqueous adhesive, and its manufacturing method
JP2009084836A